TRANSPORT OF LOW 240PU/239PU ATOM RATIO PLUTONIUM-SPECIES IN THE OB AND YENISEY RIVERS TO THE KARA SEA - Lind O.C.; Oughton D.H.; Salbu B.; Skipperud L.; Sickel M.A.; Brown J.E.; Fifield L.K.; Tims S.G. (My University, 2006)
Plutonium (Pu) isotope ratios can be used to differentiate between sources of Pu contamination such as nuclear weapon production, weapon fallout as well as accidental and routine releases from nuclear installations. To obtain information on the contamination level, speciation and sources of Pu in the Ob and Yenisey river systems (Siberia, Russia) and the adjacent Kara Sea, water was size fractionated onboard ship and the concentrations and atom ratios of 240Pu and 239Pu in obtained water fractions (i.e. particles, colloids and low molecular mass species) were determined by accelerator mass spectrometry (AMS). Results show a clear difference in speciation between high 240Pu/239Pu atom ratio Pu derived from global weapon fallout and low 240Pu/239Pu atom ratio Pu, presumably originating from weapons grade Pu. In particular, the 240Pu/239Pu atom ratios (mean 0.18 ± 0.06) for particles (> 0.45 μm) could not be distinguished from global fallout Pu (0.17-0.19), whereas for low molecular mass (LMM; < 8 kDa) species the Pu ratio was much lower than for global fallout Pu in both rivers. The difference was especially well pronounced in the Ob (mean 240Pu/239Pu atom ratio 0.052 ± 0.023), where the difference was statistically significant (paired t-test, P = 0.02, n = 4). The low 240Pu/239Pu atom ratios in filtered (< 0.45 μm) water and especially in the LMM fractions were observed at stations along the whole length of the two sampling transects, extending from the lower parts of the Ob and Yenisey Rivers and into the northern Kara Sea. This provides evidence of long-range transport of Pu from low burn-up or non-civil sources into the Arctic Ocean. Pu appears to be predominantly in a dissolved form (< 0.45 μm) throughout the investigated area. The colloidal fraction (8 kDa-0.45 μm) ranged within 24-78% in the river systems and 8-53% in the Kara Sea. Concentrations of 239,240Pu in filtered (< 0.45 μm) water were very low, ranging from 2.6 to 40.6 mBq m- 3 in the rivers, somewhat higher than in the open Kara Sea (2.4-7.7 mBq m- 3) in agreement with previously reported values. © 2006 Elsevier B.V. All rights reserved.
Keywords: AMS; GLOBAL FALLOUT; OB; SPECIATION; WEAPONS GRADE PLUTONIUM; YENISEY